Peran Pengasuhan Santri Dalam Kegiatan Layanan BK Kelompok Pada Santri Indisipliner: The Role Of Santri Care In Group BK Service Activities In Indisipliner Student - Ayu Auliya; Irman Irman (Institute for Research and Community Services Universitas Muhammadiyah Palangkaraya, 2023)
The Role of Parenting Santri in Counseling Guidance Service Activities for Indisciplined Santri in Class X Madrasah Aliyah Darunna'im is very important in Islamic boarding schools. Apart from being coaches and educators, Student Care also plays an active role in the process of group counseling service activities for indisciplined students in order to make students obedient and have good morals. the researcher formulates the problem as follows, namely, What is the Process of Fostering the Parenting Role in Group Counseling Guidance Service Activities for Indisciplinary Santri in Class X Madrasah Aliyah Darunna'im and How are the Results Achieved in the Parenting Role in Group Counseling Guidance Service Activities for Indisciplined Santri in Class X Madrasah Aliyah Darunna'im. This type of research uses a descriptive analysis research type that aims to describe and analyze the process of the Teacher's Role in Group Counseling Guidance Service Activities for Indiscipline Santri using observation, data collection, interviews and documentation methods. The findings in this study indicate a positive impact and a good change from before. By using group counseling services, using the exemplary method (uswah), the habituation method (ta'widiyah), the advice method (mau'izhah), and the disciplinary method. This method is carried out to instill moral values and social ethics both within the Pondok Pesantren and the community.